1998
DOI: 10.4269/ajtmh.1998.58.399
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in agglutination of Plasmodium falciparum-infected erythrocytes.

Abstract: Abstract. Agglutination and rosette formation are in vitro characteristics of Plasmodium falciparum-infected erythrocytes, which have been associated with host protective immune responses and also with parasite virulence. The present study was carried out in an area of seasonal and unstable malaria transmission in eastern Sudan. Plasma samples were obtained before, during, and after the transmission season from a volunteer cohort of 64 individuals seven years of age and older. These plasmas were assayed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…As a consequence, antibodies induced by infection are clone-specific. This was shown clearly by acute and convalescent sera from children (1, 4, 6, 9), sera from experimentally infected Aotus monkeys (7), and sera from individuals living in areas of low or seasonal transmission (2,3,28). Even antibodies from malaria-immune African adults are variantspecific; the same antibodies only rarely will cross-agglutinate PEs from two variant clones (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, antibodies induced by infection are clone-specific. This was shown clearly by acute and convalescent sera from children (1, 4, 6, 9), sera from experimentally infected Aotus monkeys (7), and sera from individuals living in areas of low or seasonal transmission (2,3,28). Even antibodies from malaria-immune African adults are variantspecific; the same antibodies only rarely will cross-agglutinate PEs from two variant clones (10).…”
Section: Discussionmentioning
confidence: 99%
“…For this mechanism to remain effective despite repeated exposure to P. falciparum, the response to PfEMP1 must be kept variant-specific. This is most likely done by diverting the immune response away from potential crossreactive determinants and directing it to strong, polymorphic, immunodominant epitopes (3,13,28). One such example is the CD36-binding fragment of CIDR1 that elicits antibodies by immunization in various animals but does not appear to elicit high-titer antibodies in humans or monkeys exposed to P. falciparum (refs.…”
Section: Discussionmentioning
confidence: 99%
“…This variability is afforded by the multiple copies in the genome of their coding gene, denoted var (Baruch et al 1995;Smith et al 1995;Su et al 1995). These antigens are recognized by the immune system in a highly variantspecific way (Marsh & Howard 1986;Forsyth et al 1989;Newbold et al 1992;Iqbal et al 1993;Reeder et al 1994;Giha et al 1998;Bull et al 1999;Giha et al 1999;Nielsen et al 2002;Ofori et al 2002) although there appears to be some cross-reactivity between variants (Aguiar et al 1992;Chattopadhyay et al 2003). Low titres (Marsh et al 1989) and lack of recognition by antibody to the variant expressed by the infecting type has been associated with disease severity in field studies (Bull et al 1998(Bull et al , 2000Giha et al 2000;Nielsen et al 2002).…”
Section: (B) Antigenic Variationmentioning
confidence: 99%
“…16,[23][24][25] Numerous studies have demonstrated the wide diversity of VSA. 5,6,20,[26][27][28][29][30][31][32][33] Nevertheless, VSA do contain regions that are either identical or antigenically cross-reactive, and conserved epitopes are present in PfEMP-1. 34,35 More-recent studies have confirmed that VSA contain cross-reactive epitopes, lending support to the idea that these molecules could be used in the design of antiadhesive therapeutics.…”
Section: Introductionmentioning
confidence: 99%